Gen-X vs Gen-Y: How They Perceive Work-Life Balance? - Ng, Lee Chiak; Dayang Kartini, Abang Ibrahim; Juliana, Hutasuhut (2012)
Work-life balance (WLB) is a newly discussed issue in Malaysia. Therefore, study needs to be done to understand the WLB issues in Malaysia. This study aims to find out how WLB is being perceived among the Malaysians, especially generation X and generation Y. Data collection has been carried out by using semi-structured interview with 4 informants consist of 2 generation X and 2 generation Y. Result of this study has been analyzed using content analysis. Findings from the data collection suggested that generation X and generation Y understand WLB as an involvement balance in work and life, fulfilling the responsibility in work and life, and both work and life need to be separated. This study also found that imbalance in work-life would lead to many impacts which the most significant impact is turnover intention. In term of the challenges in achieving WLB, different informant has mentioned different challenges whereby most of the challenges are related to individual factors. As overall, this study contributes to deeper understanding on WLB issues in Malaysia. Moreover, due to most of the research are done in western context, this study which is done in eastern context could serve as one of the important references for the future research on WLB in eastern countries.